Clinical outcomes of tissue expanders on adjuvant radiotherapy of resected retroperitoneal sarcoma. Issue 28 (July 2016) - Yu, Jeong Il; Lim, Do Hoon; Park, Hee Chul; Nam, Heerim; Kim, Bo Kyoung; Kim, Sung-Joo; Park, Jae Berm
Abstract : Abstract: We investigated the efficacy and safety of a tissue expander (TE) for adjuvant radiotherapy (RT) of resected retroperitoneal sarcoma (RPS). This study was conducted with 37 patients with RPS who received resection with or without TE insertion followed by RT from August 2006 to June 2012 at Samsung Medical Center. Among the 37 patients, TE was inserted in 19. The quality of TE insertion was evaluated according to the correlation of clinical target volume and retroperitoneal surface volume covered by TE and was defined as follows: excellent, ≥85%; good, 70% to 85%; fair, 50% to 70%; and poor, <50%. The median follow-up period after surgery was 47.9 months (range, 5.5–85.5 months). The quality of TE insertion was excellent in 7 (36.8%), good in 5 (26.3%), fair in 4 (21.0%), and poor in 3 (16.7%) patients. A significantly higher biologically equivalent dose (BED, α/β = 10) was used in patients who had TE insertion (median, 64.8 vs. 60.0 Gy, P = 0.01). Local control was 39.7%, and overall survival was 76.4% at 5 years. Local control was significantly higher in patients who received ≥65 Gy of BED, 100.0% in contrast to 22.8% ( P = 0.01). One patient with a history of multiple tumor resections showed abdominal infection with duodenal perforation of uncertain cause but had the potential of being related to TE and/or RT. Otherwise there were no ≥grade III acute or late toxicities. TE for adjuvant RT in RPS is feasible for delivering a higher RT dose with acceptable toxicity.